Structural Shared Leadership and Teacher Resilience in the Implementation of the Independent Curriculum - Dinda Delfina Septiarany; Meilia Rosani; Neta Dian Lestari (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
The implementation of the Independent Curriculum requires teachers to continuously adapt to changes in instructional practices, technology integration, assessment, and increasingly diverse learning needs, making teacher resilience an important capacity for sustaining professional performance . This study aims to examine the relationship between the structural dimensions of shared leadership and teacher resilience in public elementary schools during the implementation of the Independent Curriculum. A quantitative approach with an explanatory survey design was employed involving 127 teachers from 12 public elementary schools in Air Kumbang District, Banyuasin Regency, South Sumatra, Indonesia, selected through proportional random sampling. Data were collected using a 55 item questionnaire and analyzed using descriptive statistics and multiple linear regression. The findings show that participative decision making, collaborative professional practice, teacher empowerment, organizational support, and shared responsibility were positively and significantly associated with teacher resilience. Collectively, these five dimensions explained 67.9% of the variance in teacher resilience (R² = 0.679; F = 51.218; p < 0.001). Organizational support emerged as the strongest predictor (β = 0.301), followed by collaborative professional practice (β = 0.267), participative decision making (β = 0.218), teacher empowerment (β = 0.193), and shared responsibility (β = 0.176). The study contributes empirical evidence that teacher resilience during curriculum reform is associated not only with individual capacity but also with organizational leadership conditions. These findings highlight organizational support and professional collaboration as particularly relevant dimensions of shared leadership for strengthening school environments that support teacher resilience